2013
DOI: 10.2478/v10172-012-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Corrosion of Sintered Stainless Steels Used for Bipolar Plates in Polymer Exchange Membrane Fuel Cells / Wpływ Ph Roztworu Na Szybkosc Korozji Spiekanych Stali Nierdzewnych Stosowanych Na Okładki Ogniw Paliwowych Z Membrana Polimerowa

Abstract: WPŁYW pH ROZTWORU NA SZYBKOŚĆ KOROZJI SPIEKANYCH STALI NIERDZEWNYCH STOSOWANYCH NA OKŁADKI OGNIW PALIWOWYCH Z MEMBRANĄ POLIMEROWĄProton exchange membrane fuel cells (PEMFCs) are numbered among low-temperature cells. Their operating temperature reaches 120• C, whereas their efficiency amounts to ca. 40%. These cells are most often used for the batteries for portable devices, low and high power generators, stationary power plants and car drives. The PEMFCs are composed of the membrane, electrodes at both sides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…3. Figure shows a typical curves (volume vs. pressure curve) of a porous material with a hysteresis loop that is typical for spherical pores (Sintered Graphite) [15,[16][17][18]. The curves obtained for Toray Teflon and Graphite Grade, indicates that the pore shape are plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Figure shows a typical curves (volume vs. pressure curve) of a porous material with a hysteresis loop that is typical for spherical pores (Sintered Graphite) [15,[16][17][18]. The curves obtained for Toray Teflon and Graphite Grade, indicates that the pore shape are plate.…”
Section: Resultsmentioning
confidence: 99%
“…The significant part of the PEM-FC stack is the bipolar plates, which account for about 80% of total weight [1] and 45% of generator cost [2]. The requirements for a bipolar plate material are good thermal and electric conductivity, chemical stability in anodic and cathodic environ-mental, lightweight, inexpensive and easily manufactured [3,16]. By many authors, the ideal material for bipolar plates is graphite despite its brittleness and lack of mechanical strength or composites based on graphite [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the conducted research, it was observed that transitional processes in which the intermediate product was CO, the reduction of the specific surface of the catalyst caused by gas absorption was indicated, difficulties in diffusion of gases through the diffusion layer (made of carbon materials) of the electrodes were observed [25,26]. The above problems are eliminated by the use of platinum alloys with metals of transition groups in order to bind the carbon monoxide CO deposited on the platinum surface [27][28][29][30].…”
Section: Corrosion Analysismentioning
confidence: 99%
“…Products of corrosion of BP materials might poison the catalysts and decrease the efficiency of the fuel cell [39][40][41]. The working electrode was based on composite, the reference electrode was based on a saturated calomel electrode (SCE), and the auxiliary electrode was based on a Pt wire.…”
Section: Methodsmentioning
confidence: 99%